i have a question i have no idea how to solve..... Find an expression for a cubic function f if f(3) = 54 and f(-3) = f(0) = f(4) = 0. f(x) =_________________________ Does anyone know how to solve this.
Last edited by mr fantastic; September 20th 2009 at 04:52 PM. Reason: Removed excessive ! from post title, changed last line of post to lower case
Follow Math Help Forum on Facebook and Google+
Originally Posted by Sneaky i have a question i have no idea how to solve..... Find an expression for a cubic function f if f(3) = 54 and f(-3) = f(0) = f(4) = 0. f(x) =_________________________ Does anyone know how to solve this. Since you have three roots you can start by using the model where and are the known roots of the cubic. Then substitute f(3) = 54 and solve for .
Originally Posted by Sneaky i have a question i have no idea how to solve..... Find an expression for a cubic function f if f(3) = 54 and f(-3) = f(0) = f(4) = 0. f(x) =_________________________ Does anyone know how to solve this. they gave you the zeros ... f(x) = kx(x+3)(x-4) , where k is some constant and you know f(3) = 54 ... you can find out what k is
View Tag Cloud